Los sistemas de gestión de contenidos en Información y Documentación - OSUNA ALARCÓN, Mª Rosario; DE LA CRUZ GÓMEZ, Estefanía (Revista General de Información y Documentación, 2010)
An approach to the study of Content Management Systems for their significance since they are a key sector in the current Information Society. A CMS is an integrated website which allows the full realization of the documentation process, i.e. the acquisition, development, and dissemination of information in digital format, and of course permits communication between all users of the system. Furthermore, it allows content management to be carried out uniformly, and in an easily, accessible and user-friendly way. Since the adoption of the Bachelor's Degree in Information and Documentation by ANECA and its incorporation into faculties around Spain CMSs have become part of our University, their purview including the aforementioned qualification in the training of librarians, archivists, documentalists, and, for the first time, content managers.
Keywords: Content Management System; Information and Documentation; Documentalist; Content manager